Amplitude modulation atomic force microscopy based on higher flexural modes - Xilong Zhou; Rongshu Zhuo; Pengfei Wen; Faxin Li (AIP Advances, 2017)
In this work, amplitude modulation atomic force microscopy (AM-AFM) based on the higher flexural modes of the microcantilever is investigated by a numerical approach. The amplitude-distance and phase-distance curves for the first four flexural modes are obtained and compared. The dependence of phase on elastic modulus and viscosity of the sample is analyzed. Results show that a higher flexural mode yields a larger amplitude and phase in the repulsive regime and reduces the bistability, but causes a larger sample deformation and peak repulsive force. Compared to that of a lower flexural mode, the phase of a higher flexural mode provides higher sensitivity to viscosity variation for relatively large moduli.